HISTOLOGICAL STUDY OF MULTINODULAR GOITER (THYROID FOLLICULAR NODULAR DISEASE) - Wafaa Hadi AL-Hashemi (Western European Studies, 2024)
Multinodular goiter MNG It is the most common disease of the thyroid gland. It is divided into two types, the malignant MNG and the non-malignant MNG. In this research, we will discuss the non-malignant type. The histological feature under light microscope showed thick connective tissue capsule and formed multinodular: aggregation pathologic tissue of thyroid gland encapsulated that isolated from other tissue. One of the characteristics of follicles that they are characterized by varying differences in size. The large shunt is characterized by being filled with colloid which surrounded by flatted epithelial. In the second stage of MNG, hemorrhage in tissue was observed. Th addition showed degeneration change as foamy histiocytic in thyroid tissue and also see degeneration change in colloid is histiocytic . finally, the over the course of disease, tissue calcification and foci papillary hyperplastic nodule was observed.
Keywords: Identify the histological characteristics; the non-malignant multinodular